2017
DOI: 10.5007/2175-795x.2017v35n2p374
|View full text |Cite
|
Sign up to set email alerts
|

As produções de si com(o)outro: aprendizagem e produção de alteridades

Abstract: ResumoO presente ensaio procura destacar a relevância das conversações entre antropologia e educação, com especial ênfase nas noções de aprendizagem e produção de alteridades. Trata-se de um estudo teórico que opera análises de discursos em três conferências realizadas por antropólogos que estudam etnicidade. O objetivo é apresentar como a produção teórica sobre a etnicidade também é produtora de outras formas de compreensão da aprendizagem e da alteridade. Procura-se salientar a importância do aprender nas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The theoretical volume increase of the gypsum molecule, if compared with the "parent" anhydrite molecule, was challenged as a convincing explanation for the observed volume increase when gypsum precipitates. Several authors (Holliday, 1970;Ortí, 1977;Madsen et al, 1995;Pimentel 2003;Pina, 2009) have concluded that the transformation represented by equation (5.1) is an isovolumetric process in which anhydrite dissolves and then precipitates as secondary gypsum. The excess of hydrated calcium sulphate can be transported in aqueous solution or precipitated in available open spaces of the host rock.…”
Section: A Classical Interpretation For Swelling In Sulphated Formationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical volume increase of the gypsum molecule, if compared with the "parent" anhydrite molecule, was challenged as a convincing explanation for the observed volume increase when gypsum precipitates. Several authors (Holliday, 1970;Ortí, 1977;Madsen et al, 1995;Pimentel 2003;Pina, 2009) have concluded that the transformation represented by equation (5.1) is an isovolumetric process in which anhydrite dissolves and then precipitates as secondary gypsum. The excess of hydrated calcium sulphate can be transported in aqueous solution or precipitated in available open spaces of the host rock.…”
Section: A Classical Interpretation For Swelling In Sulphated Formationsmentioning
confidence: 99%
“…Other authors (Pina et. al., 2000;Krause, 1976;Pimentel, 2003) reject also the direct transformation of anhydrite to gypsum as the basic expansion mechanism. On the other hand, the analysis of field and laboratory observations indicates that the development of expansions is related with the precipitation of gypsum crystals.…”
mentioning
confidence: 99%